The Impact of Genetics on Physical Resilience and Successful Aging. (September 2015) - Resnick, Barbara; Klinedinst, N. Jennifer; Yerges-Armstrong, Laura; Choi, Eun Yong; Dorsey, Susan G.
Objective: To better understand the impact of genetics on resilience and successful aging, we tested a model of successful aging.Method: This was a descriptive study with a single interview and blood draw done with residents in a continuing care retirement community. Five genes associated with resilience were included in the model. The hypothesis was tested using structural equation modeling.Results: A total of 116 participants completed the survey. Two SNPs from SLC6A4 (rs25533 and rs1042173) and age were the only variables associated with physical resilience and explained 9% of the variance. Cognitive status, age, and depression were directly associated with successful aging; variance in rs25532 or rs1042173, resilience, and pain were indirectly associated with successful aging through depression.Discussion: Continued research to replicate these findings is needed so as to be able to recognize older adults at risk of low physical resilience and implement appropriate interventions.